2021
DOI: 10.1093/jcr/ucab024
|View full text |Cite
|
Sign up to set email alerts
|

How Resource Scarcity Influences the Preference for Counterhedonic Consumption

Abstract: Eight studies show that resource scarcity can influence consumers’ preference for counterhedonic consumption, and that the sense of control is an underlying driver of this effect. Using a large-scale field dataset covering 82 countries over a 10-year period, study 1 showed that individuals from countries with greater resources consumed horror movies to a greater extent, but this pattern was not found for other movie genres such as romance or documentary. The remaining studies used diverse experimental approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…As a result, future research is invited to investigate BM in other cultural contexts to determine if BM levels differ across countries and is expressed in the same behaviors. Initial research has, for example, suggested that counter-hedonic consumption is higher in countries with abundant resources (Yang and Zhang 2021), so such macroenvironmental factors represent an interesting avenue for future studies. Second, we measured BM at one point in time, but future research could investigate BM across time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, future research is invited to investigate BM in other cultural contexts to determine if BM levels differ across countries and is expressed in the same behaviors. Initial research has, for example, suggested that counter-hedonic consumption is higher in countries with abundant resources (Yang and Zhang 2021), so such macroenvironmental factors represent an interesting avenue for future studies. Second, we measured BM at one point in time, but future research could investigate BM across time.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we measured BM at one point in time, but future research could investigate BM across time. Indeed, while voluntary consumption of painful activities can be traced far back historically (Klein 2014), some authors seem to suggest that such consumption is increasing in magnitude in modern societies (Scott, Cayla, and Cova 2017; Yang and Zhang 2021). Importantly, it is also unclear how the pandemic has impacted BM tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…Extant research in marketing and psychology has investigated scarcity as being both objective or subjective, in which resource scarcity is defined as the real or perceived lack of financial capital that the consumer invests in order to acquire and use goods and services (Yang and Zhang 2021;Hamilton 2021;Hamilton et al 2019;Ravi and Zhu 2016;Roux et al 2015). Consistently, in this research, we define financial scarcity as the condition in which consumers are not able to obtain what they want given their real or perceived lack of financial resources.…”
Section: Financial Scarcitymentioning
confidence: 79%
“…Finally, research on counterhedonic products (products designed to evoke negative emotions for enjoyment purposes—e.g., haunted houses) finds that experiencing resource scarcity lowers preferences for counterhedonic consumption because of feelings of low control. In one interesting study, using a dataset covering 82 countries over a 10‐year period, researchers demonstrated that consumers from richer (high control) countries consumed horror movies to a greater extent than those from poorer (low control) countries (Yang & Zhang, 2022).…”
Section: Consequences Of Threats To Personal Controlmentioning
confidence: 99%
“…In one interesting study, using a dataset covering 82 countries over a 10-year period, researchers demonstrated that consumers from richer (high control) countries consumed horror movies to a greater extent than those from poorer (low control) countries (Yang & Zhang, 2022).…”
Section: Predictability Through Rules and Principlesmentioning
confidence: 99%